Comparative analysis of different RNA extraction kits used in detection of COVID-19 virus - Jhajharia, Abhishek; Bhargava, Riya; Malhotra, Bharti; Tak, Amit; Gupta, Parul (International Journal of Research in Medical Sciences, 2024)
Background: COVID-19, caused by SARS-CoV-2, was first reported in December 2019 and declared a Public Health Emergency of International Concern by the WHO. While various diagnostic methods exist, rRT-PCR remains the gold standard for detecting viral genes (N gene for SARS-CoV-2 and the E gene for all sarbecoviruses). Thus, ample RNA should be extracted for the efficient performance of the RT-PCR. Methods: We compared the specificity, sensitivity, and efficiency of three automated nucleic acid extraction kits: Perkin Elmer®, HiPurA, and Zybio. A total of 96 known NP/OP samples from a biorepository were processed using these kits according to their respective protocols. Magnetic Bead method was employed for the same, followed by rRT-PCR using Quantiplus Multiplex COVID-19 detection kit. The JASP version 0.16.2 and MATLAB 2019a were used for statistical analysis. Results: Both Perkin Elmer® and Zybio kits demonstrated 100% sensitivity, while the HiPurA kit showed 97.9% sensitivity compared to the original results. All three kits exhibited 100% specificity. Conclusions: Based on the comparison of sensitivity, specificity, efficiency, cost, turnaround time etc. Perkin Elmer® followed by Zybio are recommended as the preferred extraction kits. Both Perkin Elmer® and Zybio performed well with 100% sensitivity. This study provides alternatives in high demands during surge and in places of limited resources.